Kedudukan Lembaga Kemasyarakatan Desa dalam Penyelenggaraan Pemerintahan Desa Berdasarkan UUD NRI Tahun 1945: The Position of Village Community Institutions in the Implementation of Village Government Based on the 1945 Constitution of the Republic of Indonesia - Erga Yuhandra; Iman Jalaludin Rifa’i; Haris Budiman (UIN Kiai Haji Ahmad Sidiq Jember, 2026)
This study aims to analyze the constitutional position of Village Community Institutions (LKD) in the Indonesian state system based on the 1945 Constitution of the Republic of Indonesia, examine the legal construction of LKD in the hierarchy of laws and regulations, and analyze the implications of LKD's constitutional legitimacy on the implementation of village governance. This study uses a normative legal research method with a statutory, conceptual, and historical approach, as well as legal material collection techniques through library studies. The results of the study indicate that the constitutional position of LKD is implicit-derivative, sourced from Article 1 paragraph (2), Article 18B paragraph (2), and Article 28C paragraph (2) of the 1945 Constitution of the Republic of Indonesia. The normative construction of LKD is pyramidal-incomplete: solid at the level of laws to ministerial regulations, but weak at the constitutional and village regulation levels. Strengthening the constitutional position of the Village Fund Management (LKD) is an urgent need considering that Indonesia has more than 75,000 villages that require effective participatory institutions. Meanwhile, various empirical studies show that the authority of the LKD remains unclear, there is a lack of synchronization between Home Affairs Ministerial Regulation Number 18 of 2018 and regional regulations, and the suboptimal implementation of the empowerment function and channeling of village aspirations. These conditions indicate a gap between normative regulations and institutional implementation in the field, so that legislative reform and vertical harmonization of regulations are needed to strengthen legal certainty and the effectiveness of village governance. ABSTRAK Penelitian ini bertujuan untuk menganalisis kedudukan konstitusional Lembaga Kemasyarakatan Desa (LKD) dalam sistem ketatanegaraan Indonesia berdasarkan UUD NRI Tahun 1945, mengkaji konstruksi hukum LKD dalam hierarki peraturan perundang-undangan, serta menganalisis implikasi legitimasi konstitusional LKD terhadap penyelenggaraan pemerintahan desa. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan, konseptual, dan historis, serta teknik pengumpulan bahan hukum melalui studi kepustakaan. Hasil penelitian menunjukkan bahwa kedudukan konstitusional LKD bersifat implisit-derivatif, bersumber dari Pasal 1 ayat (2), Pasal 18B ayat (2), dan Pasal 28C ayat (2) UUD NRI Tahun 1945. Konstruksi normatif LKD bersifat piramidal-tidak lengkap: solid pada tingkat undang-undang hingga peraturan menteri, namun lemah pada tataran konstitusional dan peraturan desa. Penguatan kedudukan konstitusional LKD menjadi kebutuhan yang mendesak mengingat Indonesia memiliki lebih dari 75.000 desa yang memerlukan kelembagaan partisipatif yang efektif, sementara berbagai penelitian empiris menunjukkan masih adanya ketidakjelasan kewenangan LKD, ketidaksinkronan antara Permendagri Nomor 18 Tahun 2018 dengan regulasi daerah, serta belum optimalnya pelaksanaan fungsi pemberdayaan dan penyaluran aspirasi masyarakat desa. Kondisi tersebut menunjukkan adanya kesenjangan antara pengaturan normatif dan implementasi kelembagaan di lapangan, sehingga diperlukan reformasi legislasi dan harmonisasi regulasi secara vertikal guna memperkuat kepastian hukum dan efektivitas penyelenggaraan pemerintahan desa.